Willingness to pay for market information received by mobile phone among smallholder pineapple farmers in Benin - Arinloye, D.D.A.A.; Linnemann, A.R.; Hagelaar, G.; Omta, S.W.F.; Coulibaly, O.N.; Boekel, M.A.J.S. van (Wageningen University & Research, 2016)
Access to up-to-date information on market prices and quality requirements remains a key issue for smallholder farmers’ access to high income markets. The aim of this chapter is to explore the problem of information asymmetry between farmers and buyers in the pineapple supply chain in Benin, and to assess strategies using mobile phones to overcome this problem. Data was collected from an exploratory case study in Ghana and a survey with 285 farmers in Benin. Results show that farmers face market information asymmetry leading to lower prices and income. In Ghana, market price alerts through mobile phones messaging allowed decreasing transaction costs for farmers. In Benin, farmers expressed a willingness to pay a premium of up to US$ 2.5 per month to get market price and quality information. Econometric analysis showed that decisive factors for the size of the premium include farm location, market channel, profit margin, contact with agricultural extension services, and technical support from buyers.